Correlation Of Parental Role Models And The Role Of Pai Teachers On The Worship Discipline Of Students Of SD Al-Khotimah Semarang - Pranoto, Ahmad Hadi; Ulfatussyarifah, Ulfatussyarifah; Savana, Oseolla; Assharofi, Faiz Abdul Majid; Raharjo, Raharjo (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Parents serve as the primary role models in the family, instilling the value of worship through direct guidance and exemplary behavior. Meanwhile, teachers at school reinforce these values by providing systematic religious education. The collaboration between parents and teachers plays a crucial role in shaping students' discipline in worship. This study aims to analyze the relationship between parental role models and the role of Islamic Education (PAI) teachers in students’ worship discipline at SD Al Khotimah. Using a correlational research method with a quantitative field survey approach, data was collected through questionnaires and analyzed using multiple regression with the W-Stats program. The results indicate that parental role models significantly influence students' worship discipline, while the role of PAI teachers has a low correlation. Overall, parental role models and PAI teachers contribute 46% to students’ worship discipline, proving that both factors play a crucial role in fostering students' religious character.